Conditions of formation a common transportlogistics market EEU - Tsytovich, Nastassia N. (Journal of the Belarusian State University. Economics, 2018)
The article describes the conditions and performance of international integration processes. A preferred analysis was done for the countries of the Common Economic Union. Many factors, such as increased global competition, the liberalization of mutual trade, simplification of customs procedures, the removal of trade barriers and free movement of goods, services, labor and capital have demanded total integrated economic space. Analysed the evolutionary development of the countries in the union associations and groups, describes the stages and conditions of the common market. For EEU discussed urgent issues of the common market, as well as the trends and problems of full integration. With the regard to the transport and logistics industry, one of the most important regional markets, analysed background, nature, and the need to create a common transport and logistics market. On the basis of the targets of the industry conclusions, confirming the theoretical background and the potential of a unified transport and logistics market.
Keywords: trade agreement; a free trade area; Customs Union; common market; full integration; a common transportlogistics market EEU